2010
DOI: 10.1007/s12665-010-0716-y
|View full text |Cite
|
Sign up to set email alerts
|

Spatial variability of soil moisture at typical alpine meadow and steppe sites in the Qinghai-Tibetan Plateau permafrost region

Abstract: Permafrost degradation has the potential to significantly change soil moisture. The objective of this study was to assess the variability of soil moisture in a permafrost region using geostatistical techniques. The experiment was conducted in August 2008 in alpine steppe and meadow located in the Qinghai-Tibetan Plateau permafrost region. Four soil depths (0-10, 10-20, 20-30 and 30-40 cm) were analyzed using frequency domain reflectometry, and sampling made of 80 points in a 10 m 9 10 m grid were sampled. Soil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
35
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 25 publications
2
35
2
Order By: Relevance
“…Figures b and d also illustrate this phenomenon. The range was fluctuant during the 22 measuring occasions (Figure c), however, was significantly larger at 30 cm than at 10 and 20 cm (Table ), because SWC was lower at 30 cm than 10 and 20 cm and was more homogeneous in drier soil, consistent with the studies by Yang et al () in a similar alpine meadow on the Tibetan Plateau and by Western et al () in the Tarrawarra River catchment in Australia. C was initially stable and then increased rapidly with increasing SWC and was lowest at 5‐17% SWC (Figure ), indicating that variation caused by systemic factors, such as soil properties, vegetation, terrain, and climate, increased with SWC.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Figures b and d also illustrate this phenomenon. The range was fluctuant during the 22 measuring occasions (Figure c), however, was significantly larger at 30 cm than at 10 and 20 cm (Table ), because SWC was lower at 30 cm than 10 and 20 cm and was more homogeneous in drier soil, consistent with the studies by Yang et al () in a similar alpine meadow on the Tibetan Plateau and by Western et al () in the Tarrawarra River catchment in Australia. C was initially stable and then increased rapidly with increasing SWC and was lowest at 5‐17% SWC (Figure ), indicating that variation caused by systemic factors, such as soil properties, vegetation, terrain, and climate, increased with SWC.…”
Section: Discussionsupporting
confidence: 89%
“…Low SWCs would produce large sampling and measurement errors. C + C 0 had an apparent temporal variation at depths of 10, 20, and 30 cm, but the mean was significantly higher at 10 cm than 20 and 30 cm (Table ) and was inconsistent with the studies by Yang et al () and Li et al (), who found no apparent variation and an increasing trend with depth, respectively. Close inspection of their data indicated that the trend of the sill was consistent with that of SWC.…”
Section: Discussioncontrasting
confidence: 76%
See 2 more Smart Citations
“…[21], are based on site-scale or local survey and do not allow for the characterization of the high spatial and temporal variability at large scale of the SMC [22,23]. Remote sensing techniques can overcome these limitations as they provide better temporal and spatial coverages [24].…”
Section: Introductionmentioning
confidence: 99%